Pengaruh Stress Kerja, Promosi Jabatan dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan PT Jasamarga Related Business - Degatha Raginisa (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This research is a quantitative that aims to determine the influence of job stress, job promotion and organizational culture on employee work productivity at PT Jasamarga Related Business. This research used a sample size of 60 respondents who were all employees of the head office of PT Jasamarga Related Business. The analysis technique in this research is to use the coefficient of determination test, t test (partial) and F test (simultaneous) using SPSS version 25 software. The test result show that (1) job stress has a significant effect on the employee work productivity of PT Jasamarga Related Business, (2) job promotion has a significant effect on the employee work productivity of PT Jasamarga Related Business, (3) organizational culture has a significant effect on employee work productivity of PT Jasamarga Related Business, (4) job stress, job promotion and organizational culture simultaneously have a significant effect on employee work productivity of PT Jasamarga Related Business. Keywords: job stress, job promotion, organizational culture and work productivity.